Efficacy and Safety of "Coronary Artery Bypass Graft Angiography" with Right Transradial Access versus Left Transradial Access and Femoral Access: a Retrospective Comparative Study - Balaban,Yakup (2019)
Abstract Objective: Over the past 10 years, the rate of patients who have undergone coronary artery bypass graft (CABG) surgery has increased twofold in cases of coronary angiography. Today, transradial access is the first choice for coronary angiography. We aimed to compare the efficacy and reliability of radial versus femoral access for coronary angiography in post-CABG surgery in this study. Methods: Data from 442 patients who underwent post-CABG surgery between 2012-2017 were retrospectively compared. The right radial route was used in 120 cases, the left radial route in 148, and femoral route in 174. These three pathways were compared in terms of procedure time and fluoroscopy time, efficacy, and complication development. Comparisons among the three groups were performed with Bonferroni test for continuous variables and chi-square or Fisher's exact test for nominal variables as a binary. Results: Comparison results indicate that femoral access was better than left radial access and the left radial access was better than right radial access in terms of fluoroscopy time (10.71±1.65, 10.94±1.25, 16.12±5.28 min, P<0.001) and total procedure time (17.28±1.68, 17.68±2.34, 23.04±5.84 min, P<0.001). The left radial pathway was the most effective way of viewing left internal mammary artery (LIMA). No statistically significant differences were found among the three groups in other graft visualizations, all minor complications, total procedure and fluoroscopy time "Except LIMA imaging". Mortality due to processing was not observed in all three groups. Conclusion: The left radial route is preferred over right radial access for post-CABG angiography because the left radial pathway is close to the LIMA and is similar to the femoral pathway. In LIMA graft imaging, right radial access is a reliable route, even though it is not as effective as other pathways. We hope that the right radial pathway will improve with physician experience and innovations.